Dominican-American auto-ethnographies: considering the boundaries of self-representation in Julia Álvarez and Junot Díaz - Ibarrola Armendariz, Aitor (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2010)
This article explores some of the dilemmas faced by minority autobiographers when they set out to represent their life stories in writing. While significant benefits may be derived from this self-conscious enterprise, bicultural authors are sometimes unaware of the boundaries -or frames- that the mainstream culture demarcates for their self-portrayals. My analysis of Julia Álvarez’s ¡Yo! (1997) and Junot Díaz’s Drown (1996), which could both be characterized as ‘auto-ethnographies,’ shows how these two Dominican-American writers are subject to some of the principles and rules that have governed the genre since its very inception in the United States. Due to the kind of subjectivities and selfhoods they aspire to develop and represent in their works, and to their readers’ expectations, they are seen to deploy certain patterns and narrative techniques that can hardly be considered new or original in self-writing. Although it should be admitted that these bicultural writers have expanded the boundaries of the autobiographical genre, this article also demonstrates that these authors are dependent on a number of ‘utopian blueprints,’ divided forms of subjectivity, and conventional strategies of cultural critique that were integral to the works of the ‘forefathers’ of the genre in the New World.